2016
DOI: 10.1136/bmjopen-2015-008533
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study of barriers to cervical cancer screening among Nigerian women

Abstract: ObjectivesTo explore the barriers to cervical cancer screening, focusing on religious and cultural factors, in order to inform group-specific interventions that may improve uptake of cervical cancer screening programmes.DesignWe conducted four focus group discussions among Muslim and Christian women in Nigeria.SettingDiscussions were conducted in two hospitals, one in the South West and the other in the North Central region of Nigeria.Participants27 Christian and 22 Muslim women over the age of 18, with no dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
112
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 35 publications
16
112
3
3
Order By: Relevance
“…In previous literatures, cultural beliefs have been identified as a significant barrier (cancer as sin, the result of immorality) in women to undergo cancer screening as they prominently influence the level of understanding and knowledge about these cancers (de Cuevas et al, 2018;Gupta et al, 2015;Lee, 2015;Meana et al, 2001;Modibbo et al, 2016;Szalacha et al, 2017) and interventions addressing them have also produced results (Adunlin et al, 2019;Pratt et al, 2019). Financial concern was reported both in the current study and previous studies (Malhotra et al, 2016).…”
Section: Discussionsupporting
confidence: 58%
“…In previous literatures, cultural beliefs have been identified as a significant barrier (cancer as sin, the result of immorality) in women to undergo cancer screening as they prominently influence the level of understanding and knowledge about these cancers (de Cuevas et al, 2018;Gupta et al, 2015;Lee, 2015;Meana et al, 2001;Modibbo et al, 2016;Szalacha et al, 2017) and interventions addressing them have also produced results (Adunlin et al, 2019;Pratt et al, 2019). Financial concern was reported both in the current study and previous studies (Malhotra et al, 2016).…”
Section: Discussionsupporting
confidence: 58%
“…Shame was associated with disclosure of cervical cancer-related symptoms and screening results because it is a disease of the female reproductive system. Isa-Modibbo et al [4] also reported fear of disclosure of results and lack of awareness among the barriers to uptake of screening.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The principal barriers associated with cervical cancer screening uptake reported in the literature for developing countries such as Nigeria are mainly a low level of awareness, widespread poverty, and lack of the requisite human and material resources to support cytology-based programmes and poverty. [3,11,12] Isa-Modibbo et al [4] explored the religious and cultural barriers to cervical screening in two hospitals, from the South West and North Central regions of Nigeria. The study reported that barriers to cervical cancer screening vary by religious affiliation.…”
mentioning
confidence: 99%
“…Some of the participants in that study were from Mangochi district which is largely inhabited by Muslims. Evidence shows that Muslims have a strong belief that their wives nakedness is strictly to be seen by their husbands as such a male provider would not be ideal to perform cervical cancer screening [40][41][42].…”
Section: Factors That Affect Screeningmentioning
confidence: 99%